KINETIC MODELLING OF BIOGAS PRODUCTION FROM CO-DIGESTION OF COW DUNG AND SUGARCANE PEELS - Muhammad, Ismail; Mashi, Ahmed Lawal (FUDMA JOURNAL OF SCIENCES, 2025)
Biogas production from agricultural residues offers a sustainable pathway for renewable energy generation and waste valorization. However, optimizing substrate combinations to maximize yield and process stability remains a major challenge. This study investigated the kinetics of biogas production from cow dung and sugarcane peels to determine optimal mixing ratios and assess co-digestion performance. Compositional analysis revealed higher organic matter (86 %) and carbon content (49.88 %) in sugarcane peels compared to cow dung (44 % and 25.52 %), suggesting their potential as a primary substrate. Five digesters with varying ratios were monitored over five weeks. The highest cumulative yield (4992 cm³) was obtained with 100% sugarcane peels, while the 75:25 sugarcane peel–cow dung mixture recorded the highest 24-hour production rate (1000 cm³), highlighting synergistic benefits. Kinetic modeling using first-order and modified Gompertz equations showed reduced lag time (microbial adaptation period before significant gas production begins.) which is 2 days vs. 4 days for cow dung alone and improved methane potential, confirming the advantages of co-digestion. The novelty of this work lies in establishing sugarcane peels, an underutilized agro-waste, as a viable primary feedstock, with cow dung enhancing both yield and start-up efficiency. Optimization identified the 75:25 ratio as the most efficient configuration. Scaling up this process could significantly reduce agricultural waste, lower rural energy costs, and provide decentralized clean energy solutions. Socioeconomically, adoption at community and industrial levels can create green jobs, support energy security, and promote circular bioeconomy models in regions with abundant sugarcane production.
Keywords: Biogas; Kinetics; Co-digestion; Sugarcane peels; Cow dung